Marco de referencia para un modelo de gobierno de datos, caso de uso en una caja de compensación familiar - Tobar Ruiz, Pablo Andrés (Escuela Colombiana de Ingeniería Julio Garavito, 2021)
In a social environment where data became the differentiating factor between business success or failure, there has been a need to implement new capabilities that allow precise, exercise control and governance over the data throughout its life cycle. The government that exerts on the data from the strategic, technical and operational point of view, will have to be over time a process inherent to the operation of all types of organizations, integrating into the business and society in general. These emerging methodologies around data and information require a process of understanding and prior analysis to achieve a successful implementation; for this reason, this document proposes a framework to understand and implement a data governance program, based on the experience of a company not profit in Colombia. Different elements are addressed that will allow to develop the process of implementing a data governance model, starting with the analysis of the current situation to view the future situation; and in this way achieve decisions based on proper data management.
Keywords: Gestión de datos; Explotación de datos; Gobierno de datos; Cajas de compensación; Data management; Data use; Data governance; Not-profit company